Microvascular Outlook on the Peripapillary Area of the Unilateral Pseudoexfoliation Syndrome and Pseudoexfoliation Glaucoma: An Optical Coherence Tomography Angiography Study - Elgin, Cansu Yüksel (Cerrahpaşa Medical Journal, 2024)
Objective: The main purpose of this study was to understand the vascular changes in the presence of the visible pseudoexfoliation material (XFM) and the fellow eye of the participants in the non-glaucomatous and glaucomatous processes. Methods: This is study included 72 eyes of 36 patients with unilateral pseudoexfoliation syndrome (XFS) and 68 eyes of 34 patients with unilateral pseudoexfoliation glaucoma (XFG). Different indicators of the XFM positive and negative eyes in each group is evaluated using standard mean comparison t-tests. The XFM positive and negative eyes in both groups were also compared against each other using the Kruskal–Wallis test. Results: For retinal nerve fiber layer (RNFL) thickness (μm), in average, all quadrants, both superior and inferior hemifields, the comparison of the paired-eyes of the participants in unilateral XFS does not show any significant difference but in the unilateral XFG group all measurements were significantly different due to the glaucomatous degeneration. Similar results were obtained with radial peripapillary capillary (RPC) vessel density (vd) (%). When correlations are calculated to examine the relationship between RNFL thickness and RPC vd, significantly positive correlations were observed generally for most of the points. Conclusion: In glaucoma cases controlled with medical treatment, a decrease in the density of the RPC, correlated with RNFL thinning has been demonstrated. However, this vascular decrease could not be shown as an early sign in the presence of XFM, which is a major risk factor for glaucoma. Cite this article as: Yüksel Elgin C. Microvascular outlook on the peripapillary area of the unilateral pseudoexfoliation syndrome and pseudoexfoliation glaucoma: An optical coherence tomography angiography study. Cerrahpaşa Med J. 2024;48(1):74-80.